Ronggeng Blantek dance learning to improve teenagers' interests and talents in Taringgul Tonggoh Village - Fikri Algi Fahri; Nahla Mutiara Rini; Oetami Nur Annisa; Bambang Erawan (Universitas Pendidikan Indonesia, 2024)
Taringgul Tonggoh Village is one of the villages in Wanayasa District, Purwakarta, West Java. Many teenagers are enthusiastic about participating in dance class learning. Based on this, a community service program was carried out in the form of Kuliah Kerja Nyata (KKN), which aims to increase the interests and talents of teenagers in Taringgul Tonggoh Village by creating one of the work programs, namely dance learning classes. This program is implemented to channel their skills and interests through dance. The method used combines lecture, drill, and demonstration methods. In dance class, Ronggeng Blantek dance is taught. The dance class learning process is carried out in several stages, namely the implementation of warm-ups and body exercises before learning to dance, teaching dance movements in stages, routine practice three times a week, preparation and implementation of dance performances for the Taringgul Tonggoh Awards event as well as the Release of UPI Thematic KKN Students. The results from learning the Ronggeng Blantek dance are that teenagers can perform the Ronggeng Blantek dance at the Taringgul Tonggoh Awards event and the release of UPI thematic KKN students. Through dance learning, indirectly, they can participate in preserving Indonesian culture, especially teenagers in Taringgul Tonggoh Village. Abstrak Desa Taringgul Tonggoh merupakan salah satu desa yang berlokasi di Kecamatan Wanayasa, Purwakarta, Jawa Barat. Di desa ini banyak remaja yang antusias dalam mengikuti pembelajaran kelas tari berdasarkan hal tersebut maka diusunglah program pengabdian dalam bentuk Kuliah Kerja Nyata (KKN) yang bertujuan untuk meningkatkan minat dan bakat remaja Desa Taringgul Tonggoh dengan membuat salah satu program kerja, yaitu kelas pembelajaran tari. Program ini dilaksanakan untuk menyalurkan bakat dan minat mereka melalui seni tari. Metode yang digunakan adalah kombinasi antara metode ceramah, drill, dan demonstrasi. Dalam pembelajaran kelas tari, tarian yang diajarkan adalah tari Ronggeng Blantek. Proses pembelajaran kelas tari dilakukan dengan beberapa tahapan, yaitu pelaksanaan pemanasan dan olah tubuh sebelum belajar menari, pengajaran gerakan tari secara bertahap, latihan rutin setiap tiga kali dalam seminggu, persiapan dan pelaksanaan pementasan tari acara Taringgul Tonggoh Awards sekaligus Pelepasan Mahasiswa KKN Tematik UPI. Hasil pencapaian yang didapatkan dari pembelajaran tari Ronggeng Blantek, yaitu untuk para remaja dapat menampilkan tarian Ronggeng Blantek ini pada acara Taringgul Tonggoh Awards sekaligus pelepasan mahasiswa KKN tematik UPI. Melalui pembelajaran tari, secara tidak langsung dapat ikut serta dalam pelestarian budaya Indonesia khususnya bagi remaja di Desa Taringgul Tonggoh. Kata Kunci: Minat dan Bakat; Pembelajaran Tari Ronggeng Blantek; Tari Tradisional